(untitled) (Eurasian Journal of Ecology, 2016)
This study is aimed at the determination of pesticide-tolerant pumpkin species and related resources across the Cucurbitaе spp. to be further used for phytoremediation of pesticide-contaminated soils in Almaty region of Kazakhstan.The data have shown particular species of the Cucurbitaе grown on the soils contaminated by the pesticides which would be able to uptake DDT and HCH metabolites in amounts exceeding maximum allowable concentration almost 19 times. Eleven food pumpkin and heirloom pumpkin varieties including few giant pumpkin varieties, Cucurbita maxima Duchesne ex Lam. have been introduced in the steppe zone of Almaty region. Hybrid fruits obtained from certain combinations have been shown to reach 30.0 x 20.0 cm in size. Kazakhstan researchers are looking forward a broad collaboration on pumpkin collection, pestiside neutralization, decomposition based on phytoextraction, phytostabilization and other techniques.